2013
DOI: 10.1161/circulationaha.113.002744
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Appropriate Use on the Prognostic Value of Single-Photon Emission Computed Tomography Myocardial Perfusion Imaging

Abstract: Background-Appropriate use criteria (AUC) have been developed to aid in the optimal use of single-photon emission computed tomography (SPECT)-myocardial perfusion imaging (MPI), a technique that is a mainstay of risk assessment for ischemic heart disease. The impact of appropriate use on the prognostic value of SPECT-MPI is unknown. Methods and Results-A prospective cohort study of 1511 consecutive patients undergoing outpatient, community-based SPECT-MPI was conducted. Subjects were stratified on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 36 publications
3
68
0
3
Order By: Relevance
“…As shown in Table 2, these categorizations for PET appropriate use are similar to those found in the majority of reports with SPECT, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] although there are some reports of SPECT MPI with higher frequency of inappropriate studies. 19,27 For evaluation of the scintigraphic findings and outcomes, the authors have combined ''appropriate'' with ''uncertain'' categories, which although somewhat controversial, is consistent with the intent of these AUC-''uncertain is assumed to not provide grounds for denial of reimbursement.''…”
supporting
confidence: 72%
“…As shown in Table 2, these categorizations for PET appropriate use are similar to those found in the majority of reports with SPECT, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] although there are some reports of SPECT MPI with higher frequency of inappropriate studies. 19,27 For evaluation of the scintigraphic findings and outcomes, the authors have combined ''appropriate'' with ''uncertain'' categories, which although somewhat controversial, is consistent with the intent of these AUC-''uncertain is assumed to not provide grounds for denial of reimbursement.''…”
supporting
confidence: 72%
“…Several studies have documented high rates of inappropriate use based on published appropriate use criteria for these procedures in contemporary practice 23, 24, 25, 26, 27, 28, 29. Large, community‐based studies have documented inappropriate use rates of 45.5% for MPI23 and 34.6% for stress tests with imaging 28. Among 8996 patients undergoing diagnostic catheterization in New York, 24.9% were considered inappropriate with rates ranging from 8.6% to 48.8% across hospitals 26.…”
Section: Discussionmentioning
confidence: 99%
“…25 A significant body of literature demonstrated that appropriate MPI use enhances its acumen in risk stratification, reduces radiation risk, and improves its clinical value. [27][28][29][30][31][32][33] Physicians are faced with multiple, occasionally discordant, AUC from different organizations. For example, there is substantial discordance between the multimodality AUC for the detection and risk assessment of stable ischemic heart disease developed by the American College of Cardiology, ASNC, and several other societies and the Appropriateness Criteria set forth by the American College of Radiology (ACR).…”
Section: Appropriate Use Reportingmentioning
confidence: 99%